Christianity and social development theory - Hermawan, Sonny; Abiri, Carol (FISIP UIN SGD Bandung, 2025)
This study explores the role of Christianity in social development by examining its foundational values of love, social justice, and service to others. Employing a qualitative approach with a descriptive-analytical method, this research analyzes various sources, including policy documents, Christian theological texts, and case studies from different countries. The findings reveal that the Church plays a significant role in social development through education, healthcare, and economic empowerment, while also contributing to social reconciliation, particularly in conflict resolution and addressing social disparities. This study highlights how Christian values can serve as a basis for inclusive and sustainable social policies, despite challenges in implementation, such as cultural resistance and resource constraints. The study concludes that fostering collaboration among religious institutions, policymakers, and civil society is essential to optimizing the role of religion in promoting a more just and harmonious society. Contribution: This research bridges theoretical perspectives with practical examples, offering valuable guidance for leveraging religious values in the pursuit of social progress.